UPNM SUBSONIC WIND TUNNEL FLOW MEASUREMENTS TECHNIQUE AND CALIBRATION: English - Methal, Zinnyrah; AAT, Syahin; MRA, Rahman; MR, Saad (PERINTIS eJournal, 2023)
Numerical methods often seen as the best practice for aerodynamic research in terms of accuracy, performance, solidity and expenditure. Nonetheless, the results reliability is still strongly depending on the experimental work for better decision making. A common fundamental tool used for aerodynamic testing is wind tunnel. With this decent instrumentation, many research is able to come out with trustworthy and prospective data to simulate various kind of applications including for low Reynolds number applications. However, the topic of calibration technique of aerodynamic instrument for wind tunnel have not been discussed thoroughly for user’s proper guideline before the experiment is conducted. Therefore, this paper will explain the method of wind tunnel calibration and technique that only specific to subsonic flow, open loop and suction type wind tunnel. The wind tunnel is the property of UPNM with a test section dimension of 1 m length, 0.3 m height and 0.3 m width and capable of running up to 100 m/s airflow. This research aims to provide a better understanding of fluid flow with additional turbulent intensity information to assure flow uniformity through numerous tests. During testing, a good agreement was found for various kind of flow diagnostic tools such as pressure measurement force balance and Particle Image Velocimetry (PIV). This confirms a decent instrumentation condition and the correctness of data reduction algorithm.